PENGEMBANGAN OBJEK WISATA PANORAMA TERTINGGAL DI KABUPATEN TANAH DATAR (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2016)
This research was motivated by the development of tourism in the district of Tanah Datar in recent years has decreased mainly attraction of natural scenery. This study aims to determine what strategies can be done in the development of attractions panorama in Tanah Datar. This research is classified in a qualitative study using SWOT analysis. The data used are primary data and secondary data. Mechanical withdrawal informants using purposive sampling technique. Data were analyzed using three stages, namely; data reduction, data presentation, and conclusion. Examination of the validity of data consisting of; extension of participation, diligence in observation, and triangulation. The results show that the strategy can be done to tourism development Panorama in Tanah Datar, among others; 1) Publish that some panoramas in Tanah Datar has used biased historical attractions history. 2) Increase the promotion via its website and location map attractions Tanah Datar. 3) Perform pruning of pine trees that have been blocking the view. 4) Improved cooperation between the Regional Government (Department of Tourism, Wali Nagari with business attractions. 5) Local governments must be able to draw up a budget to allocate infrastructure and maintenance so as to increase the waiter towards tourists.Keywords: Development, attractions, Panorama